Molecular network-selected pharmacogenomics in a case of bipolar spectrum disorder. (December 2017) - Fortinguerra, Stefano; Buriani, Alessandro; Sorrenti, Vincenzo; Lenzi, Michele; Giusti, Pietro
Personal genomic analysis was used for molecular diagnosis and pharmacogenomics in a 53-year-old female suffering from alternating depressive and dysphoric episodes. A total of 52 genes and 108 SNPs were analyzed in the whole genome. Results from the pharmacogenomic analysis were consistent with the pharmacological history and indicate mutations associated with low monoaminergic tone, but also a hyperactive 5HT2A receptor, a feature that associates to a high probability of developing a bipolar condition, especially under 5-hydroxytryptamine potentiating pharmacology. This aligns with the patient developing dysphoria with high clomipramine. The pharmacokinetic genomics pointed out to some absorption, distribution, metabolism, and excretion (ADME) alterations that can lower or nullify drug's activity. A personalized regimen was proposed, with a positive outcome after 1 year.